Photo-double-ionization of Mg studied by electron-electron-coincidence experiments - Sokell, E.; Bolognesi, P.; Kheifets, A.; Bray, Igor; Safgren, S.; Avaldi, L. (American Physical Society, 2014)
The photo-double-ionization (PDI) of Mg to the Mg2+(3s−2) state has been studied by photoelectron-photoelectron-coincidence experiments at a photon energy corresponding to the excitation of the 2p→3d resonance. The equal energy sharing (E1 = E2 = 16.4 eV) as well as the complementary unequal energy (E1↔E2 = 10.4↔22.4 eV) sharing kinematics have been investigated. From the experimental results without any approximation the symmetrized gerade and ungerade amplitudes have been obtained. The experimental angular correlation patterns as well as the amplitudes are compared to CCC calculations in which the resonant process has been incorporated. The results confirm that the amplitudes of the photo-double-ionization carry the signature of the target radial wave function. The investigation of the triple differential cross sections has been then extended by simulations to a kinematics with the fixed detector at 90°, which can not be studied experimentally by the present setup. These simulations shed light on results of previous measurements on alkaline-earth-metal atoms in this kinematics, which were not consistent with the common understanding of photo-double-ionization derived from He experiments.